A class of exactly solvable free-boundary inhomogeneous porous medium flows - Howison, S; Loutsenko, I; Ockendon, J (2006)
We describe a class of inhomogeneous two-dimensional porous medium flows, driven by a finite number of multipole sources; the free boundary dynamics can be parametrized by polynomial conformal maps.